Conciliação como meio efetivo de solução de conflitos: um estudo de caso da comarca de Quixeré-CE - Santos, José Edinaldo Lima dos (Universidade Federal Rural do Semi-Árido, 2019)
This article has as its main objective to analyze conciliation as a means of exercising dispute resolution, effecting the social pacification of conflicts in the Quixeré County Court. To verify the conciliatory activity in that region and its correlation with the reduction of the time of the demands and the construction of a mentality for the practice of conciliation of the conflicts. Subsequently, the importance of conciliation was described as a means of reestablishing relations arising from conflicts. Subsequently, through statistical data, the Permanent Conciliation Nucleus was examined with a view to determining its results in the judicial service. It is observed that the result of conciliation provides a means of social harmonization of conflicts in the most varied cases filed in Quixeré County, reducing judicial controversy, forming consensual habits, contributing to judicial efficiency (in terms of meeting the demand and accumulation jurisdiction), such as the processing of proceedings and the time required for the conclusion of judgments, in line with the principles of speed and reasonable duration of proceedings.
Keywords: Conciliação; Comarca de Quixeré; Judiciário; Litigiosidade; Conciliation; County; Judiciary; Litigation; CIENCIAS SOCIAIS APLICADAS::DIREITO